Pertumbuhan bank syariah pasca pandemi Covid-19: Analisis potensi dan tantangan - Fitri, Anis Zakiyah (Maliki Interdisciplinary Journal, 2024)
This article discusses the impact of the COVID-19 pandemic on the growth of the Islamic banking sector and analyzes the potential and challenges faced by Islamic banks in dealing with the post-pandemic period. This pandemic has posed significant challenges to the global economy and the financial industry, including Islamic banks which have unique characteristics in their operations. The growth of Islamic banks is also faced with several challenges that need to be overcome. First, fluctuations in global economic conditions post-pandemic can have an impact on the financial stability and asset performance of Islamic banks. Second, adherence to sharia principles in investing and transacting remains a challenge, requiring stricter oversight to prevent potential violations. Third, competition with conventional banks also continues, and Islamic banks must be able to offer competitive services without compromising the integrity of Islamic principles. This article uses an analytical approach to describe the growth potential and challenges faced by Islamic banks after COVID-19. The latest economic and financial data will be analyzed to provide a comprehensive understanding of the situation.